A Study of Social Engineering in the Productive Economic Sector Based on Gender Mainstreaming in Realizing a Sense of Justice for Women in Yogyakarta City - Harahap, Dewi Handayani; Rakhman, Arif Kurniar; Aco, Faizal (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Women's economic empowerment is one of the indicators of an increasing development index. Three actual problems faced by women MSMEs include patriarchal social construction, infrastructure, women's access and ability to access technology, and low financial literacy and inclusion for women. The number of women MSMEs reached 60 per cent of the 519 MSMEs studied in the Yogyakarta area, but MSMEs managed by women are still subsistence in nature. The research objectives are to analyse the strengthening of access to links and networks for women in the productive economic sector based on gender strengthening, analyse the strengthening of women's roles in gaining experience and challenges in the productive economic sector based on gender strengthening and analyse the independence of women's roles in decision making in strengthening in the productive economic sector based on gender strengthening in Yogyakarta. The research method uses exploratory sequential researchers first start with the quantitative research phase. The results of this study are 1) The trend of workers in Yogyakarta City has decreased between August 2021 and August 2022; 2) Strengthening access to wider links/networks or relationships still needs to be facilitated; 3) Strengthening of gaining experience even though activities have been carried out in the form of training for skill development; 4) Business actors are still not independent in making decisions in developing their business; 5) Strengthening structuration agents who become agents of change so that they can play a role in developing their business groups and 6) The stages in the formation of structuration agents are divided into several phases. Pemberdayaan ekonomi perempuan menjadi salah satu indikator peningkatan indeks pembangunan. Tiga masalah aktual yang dihadapi oleh UMKM perempuan adalah konstruksi sosial yang patriarkis, infrastruktur, akses dan kemampuan perempuan dalam mengakses teknologi, serta rendahnya literasi dan inklusi keuangan perempuan. Jumlah UMKM perempuan mencapai 60% dari 519 UMKM yang diteliti di wilayah Yogyakarta, namun UMKM yang dikelola perempuan masih bersifat subsisten. Tujuan penelitian ini adalah untuk menganalisis penguatan akses terhadap link dan jaringan bagi perempuan di sektor ekonomi produktif berbasis penguatan gender, menganalisis penguatan peran perempuan dalam memperoleh pengalaman dan tantangan di sektor ekonomi produktif berbasis penguatan gender, dan menganalisis kemandirian peran perempuan dalam pengambilan keputusan dalam penguatan di sektor ekonomi produktif berbasis penguatan gender di Yogyakarta. Metode penelitian menggunakan eksploratori sekuensial yang diawali dengan tahap penelitian kuantitatif. Hasil dari penelitian ini adalah 1) Tren tenaga kerja di Kota Yogyakarta mengalami penurunan pada periode Agustus 2021 hingga Agustus 2022; 2) Penguatan akses link/jaringan atau relasi yang lebih luas masih perlu difasilitasi; 3) Penguatan untuk mendapatkan pengalaman meskipun sudah dilakukan kegiatan berupa pelatihan untuk pengembangan skill; 4) Pelaku usaha masih belum mandiri dalam mengambil keputusan dalam mengembangkan usahanya; 5) Penguatan structuration agent yang menjadi agen perubahan sehingga dapat berperan dalam mengembangkan kelompok usahanya dan 6) Tahapan dalam pembentukan structuration agent dibagi menjadi beberapa fase.